2015
DOI: 10.1002/etc.3221
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of human pharmaceuticals in fish across habitats of a tidally influenced urban bayou

Abstract: Though pharmaceuticals and other contaminants of emerging concern are increasingly observed in inland water bodies, the occurrence and bioaccumulation of pharmaceuticals in estuaries and coastal ecosystems are poorly understood. In the present study, bioaccumulation of select pharmaceuticals and other contaminants of emerging concern was examined in fish from Buffalo Bayou, a tidally influenced urban ecosystem that receives effluent from a major (∼200 million gallons per day) municipal wastewater treatment pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 49 publications
(98 reference statements)
0
20
2
3
Order By: Relevance
“…In contrast, no citalopram was detected in plasma and muscle tissue (Grabicova et al, 2014). The reason for finding citalopram being accumulated in muscle tissue in our study might either be due to the fact that the exposure time was longer and the test concentrations were higher than those used in other studies (Grabicova et al, 2017;Grabicova et al, 2014;Sackerman et al, 2010) or result from a diverging accumulation pattern in brown trout compared to other fish species (Du et al, 2016).…”
Section: Bioconcentrationcontrasting
confidence: 68%
“…In contrast, no citalopram was detected in plasma and muscle tissue (Grabicova et al, 2014). The reason for finding citalopram being accumulated in muscle tissue in our study might either be due to the fact that the exposure time was longer and the test concentrations were higher than those used in other studies (Grabicova et al, 2017;Grabicova et al, 2014;Sackerman et al, 2010) or result from a diverging accumulation pattern in brown trout compared to other fish species (Du et al, 2016).…”
Section: Bioconcentrationcontrasting
confidence: 68%
“…Juvenile inanga are fed on by other fish species such as trout , and are also found in the stomach contents of coastal birds . However, ionizable pharmaceuticals are not expected to appreciably biomagnify in aquatic systems . Therefore, when combined with the relatively low BCF values estimated in the present study and those reported in other studies with rainbow trout, the risk of secondary poisoning appears low.…”
Section: Discussioncontrasting
confidence: 47%
“…Of those antibiotics that are able to be phytoextracted, some have been shown to phytoconcentrate (Du et al, 2016). Those that phytoconcentrate can theoretically select for resistance in the microbiome of the plant as well as the organism that consumes/feed off the plant, despite apparently non-selective concentrations of antibiotics in the environment (Na et al, 2013; Azanu et al, 2016).…”
Section: Relevance Of Amr To Environmental Regulators?mentioning
confidence: 99%